Towards Perfluoroalkyl and Polyfluoroalkyl Substance (PFAS)-Free Energy Harvesting: Recent Advances in Triboelectric Nanogenerators for Sports Applications - Mónica P. S. Ferreira; Inês Ferreira; Vânia Pais; Liliana Leite; João Bessa; Fernando Cunha; Raúl Fangueiro (Micromachines)
Triboelectric nanogenerators (TENGs) can convert the mechanical energy of physical activities into electricity. This is particularly useful in sports applications, where physical activity can power devices such as wearables that can provide real-time feedback on athletes’ performance or health. To work, a TENG usually needs tribopositive and tribonegative materials. Currently, the vast majority of TENGs use materials containing perfluoroalkyl and polyfluoroalkyl substances (PFAS) as tribonegative materials. However, these substances pose risks to humans and the environment, which has led the European Union to consider restrictions on these compounds. For this reason, PFAS-free alternatives, such as polydimethylsiloxane (PDMS) and MXenes, need to be better explored to replace PFAS materials while aiming to achieve equal efficiency. This review will explore some of the recent advances that have been developed in the field of PFAS-free TENGs, with an emphasis on sports applications.